Negotiating youth: Growing up in inner-city Istanbul - Boratav, H.B. (My University, 2005)
Two studies examined the representations, lived experiences and subjective worlds of young people in an economically disadvantaged neighbourhood of Istanbul, Turkey. As part of a larger project, face-to-face surveys (n = 500) were conducted with young people aged 14-28, and focus groups (n =90) were carried out in the community. Along with shared difficulties and modest expectations for the future, differences were found as a function of educational and work status in how young people constructed the meaning of youth, their life satisfaction and expectations for the future, and how they negotiated the largely negative discourse about their community and the youth within. Institutional connections and particularly being within the educational system and participating in organized sports were important resources that the young people drew upon. The results point to the need to better understand the diversity of the meaning and experience of youth in different contexts. © 2005 Taylor & Francis Group Ltd.